Climatic conditions of the development of tourist and recreational activities in the Western Elbrus region - V. A. Shalnev; A. V. Lysenko (Наука. Инновации. Технологии)
Introduction. The subject of the research is the climatic conditions of the Western Elbrus region, as one of the leading factors in the recreational activity of this unique region of the North Caucasus. Already at present, more than 100 thousand organized and unorganized vacationers come here, mainly in the summer season. Moreover, the climatic features of this region have not yet been sufficiently studied. This is due to the lack of meteorological data (there is only one meteorological station in the region) and the lack of modern recreational studies of the climate of this region. Materials and methods of the research. This research was carried out on the basis of the author's field microclimatic data, available meteorological statistics, fund materials and literature data. During the recreational assessment of the region, special attention is paid to the radiation characteristics of the climate and the seasonal characteristics of meteorological elements. The results of the study and their discussion. The climatic conditions of the region are very diverse, which is determined by its complex orography, which forms a complex system of air circulation with the effect of windward and leeward slopes and determining the features of thermal fields, moisture fields, as well as changes in other climatic elements. Another important factor affecting the climate of the region is the absolute and relative altitude above sea level, which significantly affects the formation of high-altitude climatic, geobotanical and landscape zones. The variety and complexity of the relief, significant fluctuations in altitude, the originality of the regime of radiation and heat balances in combination with seasonal features of atmospheric circulation determine a wide variety of temperature fields, a complex distribution of precipitation, significant differences between the warm, growing season and cold and other climatic indicators important for tourism. Conclusions. The western Elbrus region has extremely diverse climatic conditions in comparison with other high-mountain regions on the northern slope of the Greater Caucasus, which is associated with its position on the border of the more humid western and more continental - central sectors. The combination of unique climatic characteristics and their diversity makes this region one of the most promising in the North Caucasus for the development of tourism, for the design of a balanced recreational model for the functioning of mountain areas.